Campur Kode Dalam Novel Di Kaki Bukit Cibalak Karya Ahmad Tohari - M. Rifki Aji Setiawan; Ghufroni Ghufroni; Nurchalistiani Budiana (Peneliti.net, 2022)
This study aims to determine the code mixing contained in the novel Di Kaki Cibalak by Ahmad Tohari. The data in this study are excerpts of text, sentences, and paragraphs in the novel Di Kaki Bukit Cibalak by Ahmad Tohari published by PT Gramedia with the fourth printing in june 2014 in Jakarta. Data obtained by reading or listening and note-taking techniques. This data collection is done by using content analysis technique, which is a strategy to express, understand, and capture the massage of literary work. In this case, the research subject was read repeatedly to reveal the mixed code contained in it, then the data was sorted into small units and recorded. The recording is accompained by data selection, nomely, namely data that is not is not relevan to the research construct will be left out, while the relevant data is emphasized (Underlined/boldified) to make it easier for researchers to analyze. The results of the analysis of this study indicate that the contents of the novel Di Kaki Bukit Cibalak are found in the form of; 1) insertion of 22 findings, 2) phrases with 10 findings. 3) repetition of words with 5 findings and 4) expressions/idioms with 12 findings. The results of the code-mixing analysis as a whole show that Ahmad Tohari in this storytelling uses more elements in the form of word. Mix Code, Novel on the hill Cibalak, Research, Ahmad Tohari